CAUSES, PATTERN AND MANAGEMENT OF PAEDIATRIC MANDIBULAR FRACTURES - Asif Nazir; Muhammad Imtiaz; Ayesha Gull; Rabbia Pervaiz; Samera Kiran; Touseef Zahra; Zehra Azher Jawa; Muhammad Usman Akhtar (Pakistan Oral & Dental Journal, 2020)
Paediatric mandible serves as a foundation for future aesthetics and function. Fracture of paediatric mandible institutes asymmetry, occlusal discrepancies and can lead to TMJ ankylosis. Hence paediatric mandibular fractures should be dealt with utmost care. The objective of current study was to record and compare the causes, pattern and management options of mandibular fractures among different age groups of children, reporting to tertiary care centres in Punjab. It was an analytical study carried out from 1st August 2018 to 31st July 2019. The study was carried out on 116 patients who were divided into 2 groups. In group A, 72 patients of age 10 years or less and in group B, 44 patients of age between 11-16 years were included. They were compared for the causes, patterns and management of paediatric mandibular fractures. Paediatric mandibular fractures in both groups have tendency to be bilateral and mostly favourable. Condylar fractures were the most common type of paediatric mandibular fracture. There were statistically significant differences between both groups regarding cause (P=0.043) and management (P=0.02). It was concluded that the causes and management of mandibular fractures change with the age of children.